2018
DOI: 10.3389/fpsyt.2018.00625
|View full text |Cite
|
Sign up to set email alerts
|

Maltreatment and Emotion Recognition Among Brazilian Adolescents

Abstract: The experience of maltreatment can impair child development, including changes in the process of emotions recognition, which may result in impairment of social interactions and behavioral disabilities. In order to measure the association between maltreatment and changes on emotion recognition among Brazilian adolescents, the Emotional Recognition Test on Human Faces (ERTHF) was applied to a sample of 50 adolescents who had suffered different intensities and types of abuse. The social and clinical characteristi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Childhood emotional neglect, characterized by emotional unresponsiveness, unavailability, and limited emotional interactions between parent and child, impairs empathic processing (Ardizzi et al, 2016; Locher et al, 2014; Marta et al, 2018; Russo et al, 2015). The current study was consistent with previous studies that show that childhood emotional neglect dampens empathic accuracy for positive emotion.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Childhood emotional neglect, characterized by emotional unresponsiveness, unavailability, and limited emotional interactions between parent and child, impairs empathic processing (Ardizzi et al, 2016; Locher et al, 2014; Marta et al, 2018; Russo et al, 2015). The current study was consistent with previous studies that show that childhood emotional neglect dampens empathic accuracy for positive emotion.…”
Section: Discussionmentioning
confidence: 99%
“…To date, only a few empirical studies have investigated the relationship between childhood emotional neglect and empathic accuracy. These studies found that emotional neglect damaged people's ability to recognize angry and happy emotional faces (Marta et al, 2018; Russo et al, 2015). However, existing work usually presents emotional pictures as stimuli to induce empathy, such as the facial expressions (English et al, 2018; Marta et al, 2018; Russo et al, 2015) or the eyes (Baroncohen et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations